Об источниках сказки А. М. Ремизова «Султанский финик» [A Likely Source of Remizov´s Fairy Tale “Sultanskii finik”] - Dotsenko, Sergei (Slavica Revalensia, 2016)
This article attempts to determine a likely source of Alexei Remizov’s fairy tale “Sultanskii finik” (1909). Sergei Dotsenko suggests that the list of possible sources of this erotic story includes Pushkin’s poem “Krasavitse, kotoraia niukhala tabak,” and several of Gogol’s prose texts. He also argues that these allusions served the purpose of making erotic plots less scandalous for the readership of Remizov’s time.